Persepsi Generasi-Z Dalam Penggunaan Fintech Payment - Sari, Wida Arindya; Fiorintari, Fiorintari; Ardhi, Qisthi (Eksos, 2023)
This research is motivated by the rapidly increasing development of technology which certainly makes changes in the application of technology in the financial industry and forms the era of digitalization. The government supports the formation of a cashless society in Indonesia. Financial technology (Fintech) is recognized as one of the most important innovations in the financial industry and is growing rapidly, driven in part by economics, regulation and information technology. This study uses an explanatory survey method with a quantitative approach with the acceptance theory used, namely the modification and development of the Technology Acceptance Model (TAM) theory which focuses on three factors, namely perceived usefulness, perceived ease of use, and perceived risks. There were 392 Generation Z in the Pontianak State Polytechnic Accounting Department who participated in this study. The analysis was carried out using the SmartPLS application. This study found that perceived usefulness, perceived ease of use and perceived risk have a positive relationship and influence the intention to use fintech payments in Generation Z. Keywords: Perception, Fintech, Payments, Generation Z, TAM